The role of advertising in the design of modern Кazakhstan (Journal of Philosophy Culture and Political Science, 2023)
Modern design is characterized by its various characteristics, among which graphic design occupies a special place. The answer to the question of what are the factors of its development in the cultural space is considered in the article. The mobility of a modern person creates the need to receive information «on the go». For this, the information has visual-expressive characteristics. The representation of culture as a process of objective transformation is the basis for the development of modern advertising design. As an important factor affecting the visual features of modern culture advertising has a great image potential. Advertising design is primarily associated with an aesthetic form, focusing not only on the expressive possibilities of advertising objects, but mainly on the richness of the spiritual world of a person.Advertising design is primarily related to the aesthetic form, aimed not only at the expressive possibilities of advertising objects, but mainly at the richness of the spiritual world of a person. Advertising design is a marketing tool, one of the tools for the formation of value relations in society, the lifestyle of the consumer, his image in the conditions of the formation of market relations. The advertising design is very functional. On the one hand, it unites mass production, the market, mass consumption, on the other – spiritual culture, the aesthetics of the material world, the ideas of the mass consumer about beauty. Although graphic design objects serve as an effective detail that shapes our whole life, the article discusses our own developments and design problems.Key words: design, graphics, consumer, symbol, dominant, advertising, symbol, project, visual, tectonics, object, culture, modern, product,printing, style, object, specialist.